Room temperature synthesis of low-dimensional rubidium copper halide colloidal nanocrystals with near unity photoluminescence quantum yield. Issue 1 (21st December 2020) - Vashishtha, Parth; Hooper, Thomas J. N.; Fang, Yanan; Kathleen, Deviana; Giovanni, David; Klein, Maciej; Sum, Tze Chien; Mhaisalkar, Subodh G.; Mathews, Nripan; White, Tim
Abstract : Demonstration of Rb2 CuX3 (X = Br, Cl) colloidal nanocrystals under UV light with a representation of one-dimensional Rb2 CuBr3 crystal structure. Abstract : Metal lead halide perovskite nanocrystals have emerged as promising candidates for optoelectronic applications. However, the inclusion of toxic lead is a major concern for the commercial viability of these materials. Herein, we introduce a new family of non-toxic reduced dimension Rb2 CuX3 (X = Br, Cl) colloidal nanocrystals with one-dimensional crystal structure consisting [CuX4 ] 3− ribbons isolated by Rb + cations. These nanocrystals were synthesised using a room-temperature method under ambient conditions, which makes them cost effective and scalable. Phase purity quantification was confirmed by Rietveld refinement of powder X-ray diffraction and corroborated by 87 Rb MAS NMR technique. Both samples also exhibited high thermal stability up to 500 °C, which is essential for optoelectronic applications. Rb2 CuBr3 and Rb2 CuCl3 display PL emission peaks at 387 nm and 400 nm with high PLQYs of ∼100% and ∼49%, respectively. Lastly, the first colloidal synthesis of quantum-confined rubidium copper halide-based nanocrystals opens up a new avenue to exploit their optical properties in lighting technology as well as water sterilisation and air purification.